(untitled) (Research, Society and Development, 2024)
Cannabidiol (CBD) or medicinal cannabis is used as a non-conventional therapy in epilepsy since treatment with anticonvulsant drugs and their combinations do not have the necessary effectiveness, as these alone do not control seizures. Epilepsy is caused by a temporary and reversible modification of the brain and is classified as generalized, focal, combined focal, and unknown epilepsy. Treatment with various medications does not result in seizure control, known as TRE (Treatment-Resistant Epilepsy), therefore, other possibilities have emerged, such as CBD. The objective of this review is to provide knowledge on the use of medicinal cannabis as an integrative therapy in epilepsy, based on pre-established studies and trials in epileptic patients treated with CBD, its adverse effects, efficacy, and safety. Coming from the Cannabis sativa L. plant, it is possible to extract cannabidiol and tetrahydrocannabinol (THC), the first does not have psychoactive action, while the second has hallucinogenic action, therefore, only concentrations lower than 0.2 are allowed in pharmaceutical formulations. % of THC, as it is a stimulating substance, its main effects being the sensation of relaxation, euphoria, and disfigurement of the perception of time; in addition to physical changes, including red eyes, and increased appetite.